Vocational Education and Training in Sweden. - Kuczera Małgorzata, Małgorzata; Jeon Shinyoung, Shinyoung (Paris : Organization for Economic Cooperation & Development, 2019)
One of a series of studies on vocational education and training, this review focuses on the vocational education and training (VET) in Sweden and concludes with policy recommendations. Over recent years, Sweden has launched a series of reforms to enhance involvement of social partners in VET.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Occupational training; Vocational education; Electronic books